The Effect of Giving Liquid Organic Fertilizer From Cow Blood and NPK Phonska For the Growth of Coffee Plant Seeds (Coffea arabica L.): Pengaruh Pemberian Pupuk Organik Cair (POC) Darah Sapi dan NPK Phonska Terhadap Pertumbuhan Bibit Kopi (Coffea arabica L.) - Siti Mutmainah; Mahdalena; Vanesa Patricia (Universitas Widya Gama Mahakam, 2024)
ABSTRACT The effect of giving liquid organic fertilizer of cow blood and NPK Phonska for the growth of the coffee plant seeds (Coffea arabica L.). The purpose of study is to determine the effect of liquid organic fertilizer cow’s bloods and NPK Phonska and the interaction of the two treatments for the growthof coffee seeds (Coffea arabica L.). The study was conducted in July 2023 to November 2023 and located in the research land of the Faculty of Agriculture, Widya Gama Mahakam Samarinda University, Wahid Hasyim, Sempaja Village, subdistrict North Samarinda, East Borneo.The research method uses a random group design consists of 2 factors with 4 x 4 consisting of 3 replications. The first factor is liquis organic fertilizer cow’s blood (D) consisting of 3 levels, namely: DO (Control), D1 (80 mL/L water/polybag), D2 (100 mL/L water/Polybag), D3 (120 mL/L water/polybag). The second factor in NPK Phonska (P) consisting of 3 levels, namely: P0 (control), P1 (2,5 g/polybag), P2 (3,5 g/polybag), P3 (4,5 g/polybag). Observation variable, namely growth in plant height stem diameter and number of leaft strands. The resulrs showed that liquid organic fertilizer cow’s blood gave results significant effect on plant height parameters aged 90 DAP with a dose best 100 mL/L water, NPK Phonska fertilizer gives a significant effect in the parameter the number of leaves aged 30 DAP at a dose of 4,5 g as wel the interaction between cow blood POC and NPK Phonska gives an influential result real in plant height parameters aged 30 DAP. Kata kunci : Coffea, NPK Phonska, POC